Pengaruh Pengungkapan Esg, Cash Holding, dan Asset Growth Terhadap Nilai Perusahaan Sektor Energi di Bursa Efek Indonesia - Jelita Rahelia; Murtanto Murtanto (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to examine and obtain empirical evidence regarding the effect of Environmental, Social, and Governance (ESG) disclosure, cash holding, and asset growth on firm value. The theories underlying this research are Stakeholder Theory, Agency Theory, and Signaling Theory. The population in this study includes all energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. The sample selection technique utilized purposive sampling, resulting in an initial sample of 57 companies with 228 observations. After screening for outliers, 38 extreme data points were removed, yielding a final analytical sample of 190 observations. The data analysis method employed panel data regression using EViews software. Based on the Chow test and Hausman test, the Fixed Effect Model (FEM) was selected as the most appropriate estimation model. The results show that Environmental, Social, and Governance (ESG) disclosure and Cash Holding have no effect on firm value. Meanwhile, Asset Growth has a positive effect on firm value. Simultaneously, all independent variables have the ability to explain variations in firm value by 96.58%. These findings are expected to assist investors, management, and regulators in assessing the relevance of sustainability disclosures as well as asset and cash management policies in the energy sector.